A Rare Case of Male‐to‐Eunuch Gender Dysphoria. Issue 4 (18th November 2015) - Hermann, Maria; Thorstenson, Andreas
Abstract: The aim of this case report is to improve the awareness of this gender dysphoria both for the single patient interest as well as for the community. This is a single‐patient case report. Literature search and Internet browsing for forum concerning this subject were performed. Healthcare professionals must be aware of this group of patients as they have a greater risk of self‐harm in order to self‐castrate, which could be acute and life threatening if not performed in the right way.Hermann M and Thorstenson A. A rare case of male‐to‐eunuch gender dysphoria. Sex Med 2015;3:331–333.